Cost-effectiveness analysis of first-line serplulimab combined with chemotherapy for extensive-stage small cell lung cancer - Liang, Xueyan; Chen, Xiaoyu; Li, Huijuan; Li, Yan (Frontiers in Public Health, 2023)
Background For patients with extensive-stage small cell lung cancer (ES-SCLC), serplulimab plus chemotherapy is beneficial as the first-line treatment. It is uncertain whether serplulimab plus chemotherapy will be more cost-effective. The aim of this study was to evaluate from the perspective of the Chinese healthcare system to assess the cost-effectiveness of serplulimab plus chemotherapy for patients with ES-SCLC. Materials and methods This study employed a partitioned survival model. Patients in the model were selected from ASTRUM-005 for their clinical characteristics and outcomes. In order to assess the robustness of the model, we conducted deterministic one-way sensitivity analyzes as well as probabilistic sensitivity analyzes. Subgroup analyzes were also conducted. Costs, quality-adjusted life-years (QALYs), life-years, incremental cost-effectiveness ratio (ICER), incremental net health benefits (INHB), and incremental net monetary benefits (INMB) were analyzed. Results Based on the base-case analysis, serplulimab plus chemotherapy contributed to an increase in 0.826 life-years and 0.436 QALYs; an incremental cost of $52,331, yielded ICER of $120,149/QALY. Based on the willingness to pay (WTP) threshold of $37,669/QALY and $86,569/QALY, the INHB was −0.954 QALYs and − 0.169 QALYs and the INMB was -$35,924 and -$14,626, respectively. Based on the probabilistic sensitivity analysis results, serplulimab plus chemotherapy was unlikely to be cost-effective at a WTP threshold of $37,669/QALY and $86,569/QALY. One-way sensitivity analysis indicated that cost of serplulimab and body weight had the greatest impact on the model. Serplulimab plus chemotherapy could be cost-effective at a WTP threshold of $86,569/QALY when the cost of serplulimab was less than $5.24/mg or when the weight of the patient was less than 40.96 kg. Regardless of the WTP threshold at $37,669/QALY or $86,569. Serplulimab plus chemotherapy was not cost-effective in all subgroups. Conclusion Serplulimab plus chemotherapy was not cost-effective, despite having a prior clinical benefical and a relative safety profile compared with chemotherapy. With the reduction in the price of serplulimab, ES-SCLC patients treated with serplulimab plus chemotherapy may be able to achieve a favorable cost-effectiveness rate.